Women on the Bench - Brody, Anita Blumstein; Ginsburg, Ruth Bader; Hall, Priscilla; Miller-Lerman, Lindsey; Shea, Felice K.; Uviller, Rena Katz (Columbia Journal of Gender and Law, 2003)
Good afternoon. My name is Felice Shea, and it is my great pleasure to welcome all of you to the panel entitled Women on the Bench. You will be hearing from a group of very distinguished judges who are sitting on either side of me—all graduates of this great law school. Columbia Law School has always honored its judges, both men and women. But looking back, there was a long stretch of time when Columbia Law School graduates on the bench were all men. When I graduated in 1950 from the law school, there were no Columbia women on the bench. When I was first elected to the bench twenty-five years later, in November of 1974, there were very few already there: Constance Baker Motley, Nanette Dembitz, Joan O’Dwyer, Hortense Gable, and Beatrice Shainswit. Even when joined by women judges from other law schools, we were a lonely little group. As late as 1983, when I went on the state Supreme Court, the Association of Supreme Court Judges held its dinner at a club that did not admit women members. There were too few of us to matter.